Autonomous Biogeochemical Floats Detect Significant Carbon Dioxide Outgassing in the High‐Latitude Southern Ocean. Issue 17 (5th September 2018) - Gray, Alison R.; Johnson, Kenneth S.; Bushinsky, Seth M.; Riser, Stephen C.; Russell, Joellen L.; Talley, Lynne D.; Wanninkhof, Rik; Williams, Nancy L.; Sarmiento, Jorge L.
Abstract: Although the Southern Ocean is thought to account for a significant portion of the contemporary oceanic uptake of carbon dioxide (CO2 ), flux estimates in this region are based on sparse observations that are strongly biased toward summer. Here we present new estimates of Southern Ocean air‐sea CO2 fluxes calculated with measurements from biogeochemical profiling floats deployed by the Southern Ocean Carbon and Climate Observations and Modeling project during 2014–2017. Compared to ship‐based CO2 flux estimates, the float‐based fluxes find significantly stronger outgassing in the zone around Antarctica where carbon‐rich deep waters upwell to the surface ocean. Although interannual variability contributes, this difference principally stems from the lack of autumn and winter ship‐based observations in this high‐latitude region. These results suggest that our current understanding of the distribution of oceanic CO2 sources and sinks may need revision and underscore the need for sustained year‐round biogeochemical observations in the Southern Ocean. Plain Language Summary: The Southern Ocean absorbs a great deal of carbon dioxide from the atmosphere and helps to shape the climate of Earth. However, we do not have many observations from this part of the world, especially in winter, because it is remote and inhospitable. Here we present new observations from robotic drifting buoys that take measurements of temperature, salinity, and other water properties year‐round. We use these data to estimate the amount of carbon dioxide being absorbed by the Southern Ocean. In the open water region close to Antarctica, the new estimates are remarkably different from the previous estimates, which were based on data collected from ships. We discuss some possible reasons that the float‐based estimate is different and how this changes our understanding of how the ocean absorbs carbon dioxide. Key Points: Measurements from biogeochemical profiling floats were used to estimate air‐sea fluxes of carbon dioxide Significant annual net outgassing of carbon dioxide was observed in the high‐latitude Antarctic‐Southern Zone In this region, a large difference with previous estimates was found in winter when ship‐based sampling is sparse